Handbook of marketing scales multi-item measures for marketing and consumer behavior research - Bearden, William O., 1945- (SAGE, 1999)
'The Handbook of Marketing Scales' is a compilation of multi-item, self-report measures developed and/or frequently used in consumer behavior and marketing research. Over 150 scales are included in the handbook, many of which were originally published in marketing- and consumer-related journals or conference proceedings.